Slack Wax Deoiling by Static Crystallization - Pronchenkov, I. A.; Antonov, S. A.; Matveeva, A. I.; Bartko, R. V.; Nikulshin, P. A.; Kilyakova, A. Yu; Tonkonogov, B. P.; Dogadin, O. B. (Chemistry and technology of fuels and oils, 2022)
The possibility of producing semi-purified and deeply deoiled paraffins from slack waxes by the method of static crystallization is investigated. Optimal parameters of a one-stage deoiling process for obtaining semi-purified paraffins with an oil content of less than 3 wt% were determined. The potential of a two-stage deoiling process for production of deeply deoiled paraffins with an oil content of less than 1 wt% was demonstrated. The economic efficiency of the proposed methodology of slack wax deoiling by static crystallization was confirmed by calculations.